The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1001/archneur.55.12.1524
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Radiosurgery for Trigeminal Neuralgia

Abstract: Gamma knife radiosurgery is a minimally invasive technique to treat trigeminal neuralgia. It is associated with a low risk of facial paresthesias, an approximate 80% rate of significant pain relief, and a low recurrence rate in patients who initially attain complete relief. Longer-term evaluations are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
4
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(125 citation statements)
references
References 25 publications
7
111
4
2
Order By: Relevance
“…16 The initial response rates in our patients are comparable to those reported in the majority of previous studies of GKS. [4][5][6][12][13][14][15][30][31][32] The effect of the latency period after SRS in our study is comparable with the findings in previously reported series. 8,17,22,23,29,31 Interestingly, patients with previous surgery seem to be more frequently late responders to GKS than patients with no history of previous surgery.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…16 The initial response rates in our patients are comparable to those reported in the majority of previous studies of GKS. [4][5][6][12][13][14][15][30][31][32] The effect of the latency period after SRS in our study is comparable with the findings in previously reported series. 8,17,22,23,29,31 Interestingly, patients with previous surgery seem to be more frequently late responders to GKS than patients with no history of previous surgery.…”
Section: Discussionsupporting
confidence: 91%
“…However, other clinical investigators have reported lower incidence rates of posttreatment facial numbness. 10,15,17,23,29 The development of numbness was slightly higher in the group of patients with previous surgery in our study. However, this difference was not statistically significant.…”
Section: Neurosurg Focus / Volume 23 / December 2007contrasting
confidence: 41%
See 1 more Smart Citation
“…Furthermore, very small collimators (4-8 mm at isocenter) and high single doses between 100 and 200 Gy were necessary for this kind of treatment [23,28,54]. Treatment of trigeminal neuralgia by radiosurgery has become a common indication in the last few years [31,36,39,42]. This technique can achieve comparable results as more invasive treatment techniques for facial pain (Figure 2).…”
Section: Functional Radiosurgerymentioning
confidence: 99%
“…The Gamma Knife has historically been the "Gold-Standard" for the radiosurgical lesioning of trigeminal neuralgia (TN) [1][2]. By administering 60-90 Gy with a Co-60 source through a 4 mm aperture, the Gamma Knife has been shown to produce conformal isodose distributions and correspondingly excellent clinical results [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%